Synthesis and Characterization of 8-Hydroxyquinolone-Melamine-Formaldehde Terpolymers - Gurnule, W.B.; Juneja, H.D.; Paliwal, L.J. (Asian Journal of Chemistry, 2010)
The terpolymer resins have been synthesized by the condensation of 8-hydroxyquinoline (Q) with melamine (M) and formaldehyde (F) in the presence of 2M HCl as catalyst. Four different types of 8-HQMF terpolymer resins with different stoichiometry have been synthesized by taking different molar ratios of 8-hydroxyquinoline : melamine: formaldehyde as (1 : 1 : 3), (2: 1 : 3), (3: 1 : 5) and (4: 2 : 7). The terpolymer resins were purified by suitable method. The terpolymers were characterized by elemental analysis, UV-visible, infrared and 1H NMR spectral studies. The number average molecular weights of terpolymers resins have been determined by conductometric titrations in non-aqueous medium and vapour pressure osmometry (VPO). Viscometric measurements in dimethylformamide (DMF) have been carried out in order to ascertain the characteristic functions and constants of terpolymer resins. The structures of the terpolymer resins have been established by analytical and spectral data.